2016
DOI: 10.21909/sp.2016.01.706
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Executive Functions and Flow in Learning

Abstract: Abstract:The aim of the study is to assess the relationship between executive functions and flow experiences in learning. Female college students assessed their flow in learning activities and performed phonemic verbal fluency task (PVF) and a lexical Stroop task. Flow in learning was associated with performance on the PVF task, but not with the lexical Stroop task. In addition, flow in learning mediated the effects of verbal fluency performance on the Grade Point Average (GPA), while inhibition and controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…As expected, the present study also showed that the only significant predictor of academic achievement for both groups was flow in academic activities. This result is in line with previous studies showing the association between flow in learning and academic achievement (Engeser et al, 2005;Ljubin Golub et al, 2016a). Flow in academic activities, leisure and routine activities can explain 7% of the variance of nonworking students' academic achievement and 11% of the variance of part-time working students' academic achievement.…”
Section: Flow In Different Domains As Predictors Of Students' Well-besupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, the present study also showed that the only significant predictor of academic achievement for both groups was flow in academic activities. This result is in line with previous studies showing the association between flow in learning and academic achievement (Engeser et al, 2005;Ljubin Golub et al, 2016a). Flow in academic activities, leisure and routine activities can explain 7% of the variance of nonworking students' academic achievement and 11% of the variance of part-time working students' academic achievement.…”
Section: Flow In Different Domains As Predictors Of Students' Well-besupporting
confidence: 92%
“…Flow was shown to be associated with higher efficiency. In an educational context, it was shown that flow in learning is positively related to higher GPA (Ljubin Golub, Rijavec, & Olčar, 2016a;Schiefele & Csikszentmihalyi, 1995). Also, flow predicted students' performance (Engeser & Rheinberg, 2008) even when students' initial abilities and GPA were controlled (Engeser, Rheinberg, Vollmeyer, & Bischoff, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies which are trying to find the protective factors are beginning to emerge. Experiencing flow is associated with increased students well-being (Asakawa, 2010;Rijavec, Ljubin-Golub, Jurčec, & Olčar, 2017), academic success (Engeser et al, 2005;Ljubin-Golub et al, 2016), and is negatively related to burnout , and thus may be a protective factor for burnout. However, the role of flow experienced in different domains, i.e., academic domain and leisure domain as protective factors of academic burnout is not yet researched in longitudinal design.…”
Section: Problem Statementmentioning
confidence: 99%
“…Although flow research started with activities that are usually associated with leisure, later research showed that flow experiences also happen during obligatory activities, such as work (Csikszentmihalyi & LeFevre, 1989;LeFevre, 1988) and studying (Carli et al, 1988;Rijavec et al, 2016). In an academic setting, flow is related to higher commitment, motivation, achievement, and persistence (Ljubin Golub et al 2016;Shernoff et al, 2003;Shernoff & Hoogstra, 2001;Shernoff & Schmidt, 2008) and to a better understanding of the presented material (Culbertson et al, 2015). However, previous research has shown that flow during academic work is less frequent than flow during leisure activities.…”
Section: General Introductionmentioning
confidence: 99%